THE TECHNIQUES USED IN THE ENGLISH LANGUAGE TEACHING AND THEIR INCIDENCE ON THE READING AND SPEAKING SKILLS WITH THE STUDENTS OF EIGHTH , NINTH , TENTH YEARS OF BASIC EDUCATION, AFTERNOON SECTION AT THE PIO JARAMILLO ALVARADO HIGH SCHOOL OF THE CITY OF LOJA, ACADEMIC YEAR 2007-2008 - Cuenca Quiñonez, Edwin Homero (2009)
In the researching process about "The teaching techniques used by the teachers and their incidence on the reading and speaking skills of English, the survey and the direct observation were applied to gather the data and the scientific, descriptive, deductive, inductive and analytical- synthetic methods were used to guide the research process. The main problems that were found in the researching work are the following: the teachers did not apply appropriate techniques, the teachers were confused among techniques and types of reading and speaking, the teachers did not encourage to students to read extra materials, on other hand the students have a low level in the development of the reading and speaking skills. With the finality to solve these problems it is proposed that the teachers attend some seminaries and training courses to learn the manage, use and application of the appropriate techniques especially into the reading and speaking skills.